2012
DOI: 10.1016/j.juro.2011.12.100
|View full text |Cite
|
Sign up to set email alerts
|

Half of Visible and Half of Recurrent Visible Hematuria Cases Have Underlying Pathology: Prospective Large Cohort Study With Long-Term Followup

Abstract: Almost 50% of patients presenting with visible hematuria will have a diagnosis. Therefore, all cases of visible hematuria require full standard investigations. Patients with no diagnosis can be discharged from followup. Recurrent visible hematuria after full initial negative findings requires repeat full standard investigations because 11.6% will have malignant pathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 10 publications
1
21
0
Order By: Relevance
“…Haematuria is an extremely common presenting symptom for urological malignancy and many papers have been published regarding its PPV in diagnosing urological cancer. [3][4][5][6][7][8][9][10] However, most of the evidence involved patients who were reviewed electively in an outpatient setting. There are scant data assessing the diagnostic value of VH in the emergency setting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Haematuria is an extremely common presenting symptom for urological malignancy and many papers have been published regarding its PPV in diagnosing urological cancer. [3][4][5][6][7][8][9][10] However, most of the evidence involved patients who were reviewed electively in an outpatient setting. There are scant data assessing the diagnostic value of VH in the emergency setting.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Prospective cohort studies in United Kingdom (UK) protocol-driven haematuria clinics have revealed an incidence of malignant pathology in 19%-24% of patients with VH vs 3.7%-5.2% for non-visible haematuria. [5][6][7][8] The majority of malignancies found are urothelial carcinoma (UC) of the bladder.…”
Section: Introductionmentioning
confidence: 99%
“…To determine the significance of the organisation of haematuria diagnostic evaluation, we enumerated the prostate cancer prevalence for studies reporting results from specialised haematuria clinics (n = 12) [21,23,[25][26][27]29,38,[54][55][56][57][58]. In the remaining studies (n = 30), haematuria was handled in general urology departments, other hospital departments, or by GPs, and in some studies the setup was not described.…”
Section: Attending a Haematuria Clinicmentioning
confidence: 99%
“…Consider re-referring these patients. A prospective large cohort study with long term follow-up found that investigations of recurring visible haematuria with previously negative findings resulted in diagnoses of urological malignancies in up to 11% of patients 15…”
Section: What You Should Domentioning
confidence: 99%